Pengaruh Komunikasi Interpersonal di Sekolah dan Kepercayaan Diri terhadap Hasil Belajar Ekonomi Siswa Kelas XI SMK N 1 Sijunjung - Muthavia, Anna; Tanjung, Mirna; Dewita Hia, Yulna (Pendidikan Ekonomi, 2014)
ABSTRACT This study aims to identify and analyze on the effect of interpersonal communication in school and the confidence of the results of class X student studying economics SMK N 1 Sijunjung . The method used in this research is descriptive method associative . The study population was all students of class X which totaled 197 students . The sampling technique is using Proportional random sampling technique , the research data were collected through a questionnaire using a Likert scale that has been on test validity and reliability testing . The analysis technique used is descriptive and inductive , which consists of test for normality , heteroscedasticity and autocorrelation multicollinearity . Testing done with SPSS version 16.0. The results of this study indicate that : 1 . Interpersonal communication in schools have a significant effect on learning outcomes economy class X students of SMK N 1 Sijunjun , 2 . Belief significant effect on student learning outcomes economy class X students of SMK N 1 Sijunjung , 3 . Interpersonal Communication in school and self Belief jointly significant effect on learning outcomes economy class X SMK N 1 Sijunjung . Based on these results , it is suggested that students , teachers and school authorities to pay more attention in school anymore interpersonal communication and self belief of students in the learning process in an effort to optimize the results of class X student studying economics SMK N 1 Sijunjung .